Stock assessment of the pharaoh cuttleflsh Sepia pharaonis Ehrenberg - Nair, K Prabhakaran; Srinath, M; Meiyappan, M M; Rao, K Satyanarayana; Sarvesan, K; Vidyasagar, Kuber; Sundaram, K S; Rao, G Syda; Lipton, A P; Natarajan, P; Radhakrishnan, G; Mohamed, K S; et al. (Indian Journal of Fisheries, 2011)
The data collected during 1979 to 1989 at different centres on both the coasts of India, indicate that the landings of the cuttlefish Sepia pharaonis Ehrenberg, increased by 3 times (11,000 t in 1989). Over 84% was from the west coast, with Maharashtra accounting for 44% and Kerala 33%. About 87% of cuttlefish is obtained in trawl net as by-catch, while a small portion is taken in localized hand-jigging operation. On the east coast over 63% of the total catch is during the second and third quarters of the year (April-September). On the west coast the fourth quarter is the most productive (50%), the second quarter being the least. The natural mortality (M) ranges from 1.08 to 1.8 iot males and 1.23 to 2.05 for females on the east coast; on the west coast the corresponding values were 1.41-2.35 and 1.5 - 2.5. On both the coasts the M for females was higher than for males. On the east coast the maximum values of fishing mortality (’F’ in the range 1.65-2.9 in male cuttlefish) was observed at a size of 170 mm; for females it is at 190 mm in the range 1.95 - 2.8. On the west coast it is at a uniform size of 190 mm in the range 1.27 - 2.14 in males and 1.33 -1.66 in females. The standing stock of male cuttlefish is higher than that of females on the east coast, while the reverse is true for the west coast. Using Thompson and Bell long-term forecast analysis the MSY and mean biomass at different M/K levels are also estimated for males and females separately for each coast. Tlie present level of exploitation is considered to be optimal on the east coast, whereas on the west coast there is scope for increase.